Conditions for the formation of the marketing environment of the enterprise - Belova, Tatyana; Dubinska, Oksana (My University, 2020)
The article is devoted to the conditions of formation of the marketing microenvironment of the enterprise operating in the agricultural market of Ukraine. Any company operates in an environment that in some way affects it. This impact is difficult to overestimate, as its effects can be both positive (and need to be developed and protected) and negative (they need to be considered and tried to overcome). The components of the marketing microenvironment are considered and their characteristics are given. Стаття присвячена умовам формування маркетингового мікросередовища підприємства, що працює на аграрному ринку України. Будь-яке підприємство працює в середовищі, яке певним чином впливає на нього. Такий вплив важко переоцінити, оскільки його наслідки можуть бути як позитивними (і їх потрібно розвивати, так і захищати) та негативними (їх потрібно враховувати і намагатися подолати). Розглядаються компоненти маркетингового мікросередовища та даються їх характеристики.
Keywords: кафедра маркетингу; marketing environment; marketing microenvironment; suppliers; intermediaries; competitors; consumers; contact audiences; маркетингове середовище; маркетингове мікросередовище; постачальники; посередники; конкуренти; споживачі; контактні аудиторії